ANALISIS PENERIMAAN PENGGUNA APLIKASI SIAPEL-TEGAS PADA LAYANAN AKTA KELAHIRAN MENGGUNAKAN TAM DENGAN KONSTRUK TRUST - Arik Mauluchi; Ahsanun Naseh Khudori; Risqy Siwi Pradini (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
SIAPEL-TEGAS is a digital public service application developed by the Malang City Government to facilitate online birth certificate registration, yet its level of user acceptance has not yet been empirically determined. This study analyzes user acceptance of the SIAPEL-TEGAS application using the Technology Acceptance Model (TAM) framework extended with the Trust construct. A quantitative approach using PLS-SEM (SmartPLS 4) was applied to 100 active users in Malang City selected through purposive sampling. The variables examined include Trust, Perceived Ease of Use, Perceived Usefulness, and Behavioral Intention to Use. Results indicate that all hypotheses were accepted, with Trust as the strongest predictor of Perceived Ease of Use. Perceived Ease of Use significantly influenced both Perceived Usefulness and Behavioral Intention to Use, while Perceived Usefulness also significantly affected Behavioral Intention to Use. The model explained 68.9% of the variance in Behavioral Intention to Use with strong predictive relevance. These findings confirm that user trust is a key factor in digital public service acceptance, and administrators are advised to prioritize system security and interface usability of the SIAPEL-TEGAS application.